2012
DOI: 10.1128/mcb.06637-11
|View full text |Cite
|
Sign up to set email alerts
|

Transient Neonatal Diabetes Mellitus Gene Zac1 Impairs Insulin Secretion in Mice through Rasgrf1

Abstract: The biallelic expression of the imprinted gene ZAC1/PLAGL1 underlies ϳ60% of all cases of transient neonatal diabetes mellitus (TNDM) that present with low perinatal insulin secretion. Molecular targets of ZAC1 misexpression in pancreatic ␤ cells are unknown. Here, we identified the guanine nucleotide exchange factor Rasgrf1 as a direct Zac1/Plagl1 target gene in murine ␤ cells. Doubling Zac1 expression reduced Rasgrf1 expression, the stimulus-induced activation of mitogen-activated protein kinase (MAPK) and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 62 publications
1
29
0
1
Order By: Relevance
“…However, the mechanisms underlying such connectivity remained incompletely understood. In this regard, we recently showed that Zac1 directly represses the paternally imprinted gene Rasgrf1, leading to an inhibition of glucose-stimulated insulin secretion in pancreatic ␤ cells (23). Here, we show that imprinted genes can also be connected via regulatory networks that involve proneural factors such as Tcf4.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the mechanisms underlying such connectivity remained incompletely understood. In this regard, we recently showed that Zac1 directly represses the paternally imprinted gene Rasgrf1, leading to an inhibition of glucose-stimulated insulin secretion in pancreatic ␤ cells (23). Here, we show that imprinted genes can also be connected via regulatory networks that involve proneural factors such as Tcf4.…”
Section: Discussionmentioning
confidence: 93%
“…The mouse C17.2 NSC line was cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum (FCS) (both from Life Technologies GmbH, Darmstadt, Germany). Tetracycline (Tc)-regulated Zac1 expression in C17.2 cells was established, and proliferation was measured as described previously (21,23). The mouse embryonic stem cell (ESC) line 46C was grown, and neuronal differentiation was performed as reported previously (25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anke Hoffmann и Dietmar Spengler [31] в экспе-рименте показали, что при лечении гипергликемии, вызванной гиперэкспрессией гена Zac1, могут быть эффективными глюкагон и агонист рецепторов глю-кагон-подобного протеина 1 (GLP-1R) лираглутид.…”
Section: äðóãèå íàïðàâëåíèÿ ìåäèêàìåíòîçíîãî ëå÷åíèÿunclassified